KAJIAN HUKUM TERHADAP KETERLAMBATAN PELAPORAN PAJAK MASA PAJAK PERTAMBAHAN NILAI DITINJAU DARI UNDANG-UNDANG NOMOR 42 TAHUN 2009 TENTANG PAJAK PERTAMBAHAN NILAI DAN PAJAK PENJUALAN ATAS BARANG MEWAH - Bayu Indra Saputra (Journal of Law ( Jurnal Ilmu Hukum ), 2020)
ABSTRACTTax is a compulsory contribution by the state that can be imposed, which aims at public expenditures related to the state's task of administering government. Not only are taxpayers obligated to pay dues or taxable entrepreneurs are also obliged to provide correct and timely tax returns in submitting the tax report. But the tax reporting process, there are still many taxable entrepreneurs who are negligent or late in submitting the report. The problem raised in this paper is how the mechanism for reporting Value Added Tax on Value Added Tax and Sales Tax on Luxury Goods and How Sanctions against taxpayers who are late in reporting the Value Added Tax period. The type of research used is normative juridical research, library research with the problem approach used in writing this thesis is the statutory approach. The results of the research show that the mechanism of reporting the value added tax that has been made by the government is quite easy to do by taxpayers, especially taxable entrepreneurs. Then the application of sanctions for taxable entrepreneurs who are late to report value added tax is subject to sanctions in the form of administrative sanctions that are still quite mild.